Does a Lack of Awareness of Cycloid Psychosis Hamper Adequate Treatment for Patients Suffering From This Disorder? A Case Report - Hausmann, Armand; Dehning, Julia; Heil, Michel; Mauracher, Laurin; Kemmler, Georg; Grunze, Heinz (Frontiers in Psychiatry, 2020)
Categorial systems of nosology are based on a cross-sectional enumeration of symptoms with a predefined cut-off, but hardly capture rapid fluctuations of manifestation nor longitudinal characteristics, e.g., cyclicity. Especially with disorders presenting with an admixture or frequent change of psychotic and affective symptoms, diagnostic specifity of the DSM and ICD diminishes. In those instances, alternative concepts as cycloid psychosis might display more accurately the very characteristics and course of a mental disorder and help to tailor individualized treatments. Karl Leonhard described three major subtypes of cycloid psychosis: anxiety–happiness psychosis, confusion psychosis, and motility psychosis, all showing a pleiomorphic symptom profile resembling intraphasic switching of poles. Here we present the case of a 59-year-old woman suffering from cycloid psychosis as defined by the criteria of Perris. Between 2013 and June 2019, the patient was admitted 35 times for compulsory treatment. A frequent change of diagnoses, ranging from adjustment disorder to complex PTSD, and from unipolar depression to “pseudoneurotic schizophrenia,” resembles the puzzling manifestations. Most of the time the patient was labeled as schizoaffective disorder despite never displaying clear psychotic core symptoms. Despite treatment with different antipsychotics including LAI the cumulative length of hospitalization increased steadily from 74 days in 2014 to 292 days in 2017. When reviewing the case in 2017 the longitudinal pattern of her disorder and the diverse acute manifestations were finally conceptualized as a cyclic on-off of an atypical psychosis. After starting lithium to pre-existing LAI antipsychotics and valproic acid, the number of days per year spent in inpatient care sharply dropped to 136 in 2018. We propose to reconsider cycloid psychosis as a useful clinical concept whose descriptive value, validity and utility for treatment decisions should be further evaluated. Lithium alone or in addition to valproic acid may act on cyclicity as a core symptom of cycloid psychosis as well as of bipolar disorder, even in the absence of major affective symptoms.